Mapping of lymph node dissection determined by the epicenter location and tumor extension for esophagogastric junction carcinoma - Liang, Rong; Bi, Xiaogang; Fan, Daguang; Du, Qiao; Wang, Rong; Zhao, Baoyu (Frontiers in Oncology, 2022)
Backgrounds: Previous studies identified the extent of lymph node dissection for esophagogastric junction (EGJ) carcinoma based on the metastatic incidence. The study aimed to determine the optimal extent and priority of lymphadenectomy based on the therapeutic efficacy from each station. Methods: The studies on the lymph node metastasis (LNM) and therapeutic efficacy index (EI) for EGJ carcinomas were identified until December 2019. The obligatory stations with the LNM rates over 5% and therapeutic EI exceeding 2% should be routinely resected for D2 dissection, while the optional nodes with EI between 0.5% and 2% should be resected in selective cases. Results: The survey yielded 16 eligible articles including 6350 patients with EGJ carcinoma. The metastatic rates exceeded 5% at No.1, 2, 3, 7, 9, 11p, 110 stations, whereas less than 5% in abdominal No.4sa~6, 8a, 10, 11d, 12a, 16a2/b1 and mediastinal No.105~112 stations. Consequently, obligatory stations with EI over 2% were largely determined by the epicenter location, and located at the upper perigastric, lower mediastinal and suprapancreatic zones, corresponding to those with rates of LNM over 5%. Consistent with the LNM rates less than 5%, the optional stations with EI between 0.5% and 2% were largely dependent on the degree of tumor extension toward the lower perigastric, splenic hilar, paraaortic and middle or upper mediastinal zones. Conclusions: The obligatory stations can be resected as an “envelope-like” wrap by transhiatal proximal gastrectomy with lower esophagectomy, whereas the optional stations for dissection are indicated by the tumor extension. The extended gastrectomy is required for the lower perigastric and paraaortic dissection in the Stomach-predominant tumor with gastric involvement exceeding 5.0 cm, while transthoracic subtotal esophagectomy is required for complete mediastinal dissection and adequate negative margin in the Esophagus-predominant tumor with esophageal invasion exceeding 3.0 cm.